Circular economy and environment: an economic and financial evaluation for the installation of an electrical and electronic devices recycling plant in the city of Bahía Blanca, Argentina - Diez, José Ignacio (2024)
[Introduction]: Within the framework of the current capitalist system, human beings have become an important polluting agent. Current production and consumption processes do not consider the existence of finite natural resources and a planet incapable of processing the waste that the existing way of life generates. Given these circumstances, the study of non-linear models is of interest, which make a more rational use of the waste that the productive activity generates, favoring recycling mechanisms. The phenomenon of recycling becomes particularly relevant in the case of electrical and electronic devices, whose ability to be degraded and metabolized by planet Earth is extremely difficult. [Objective]: Evaluate the feasibility of installing and starting a recycling plant for electrical and electronics items in the town of Bahía Blanca (Argentina), during 2021. [Methodology]: The conventional method for evaluating investment projects was used, considering technical, legal and economic aspects. [Results]: The project is not acceptable according to the profitability intended by the investor. The possibility of financing was also included, which made the project even less profitable, and the sensitivity of the results was measured, finding that the price should be 1.48 % higher than that used in the analysis. [Conclusions]: Other alternatives must be explored to make the project profitable from an economic and financial point of view.